Ensino do sistema CAD-CAM em cursos de graduação em odontologia de uma capital brasileira: estudo transversal - Eduardo da Silva von Zastrow Moura (2023)
The CAD (computer-aided design) -CAM (computer-aided manufacturing) system is becoming increasingly embedded in the dental routine, and its integration into clinical practices is increasing as new trends and demands emerge. In addition, this technology has been shown to be an important educational tool, capable of helping the development of students' skills. Therefore, the aim of this study was to assess the teaching-learning process of CAD-CAM technology at dental schools in Belo Horizonte, Brazil. This was a cross-sectional, epidemiological and descriptive study conducted with Dentistry (D) and Prosthodontics/Oral Rehabilitation (PD) professors from dental courses in Belo Horizonte, Brazil. The instrument was an online questionnaire, pretexted and validated, sent between April and May 2023, consisting of questions covering demographic aspects, academic training and teaching. The study was approved by the CEP UFMG (CAAE: 60696122.5.0000.5149). Of the 14 school, 01 did not participate. The sample consisted of 52 (100%) professors, of whom 30 (57.7%) were male and 22 (42.3%) were female, with a mean age of 44.21 (±9.11) years, mean time since graduation of 21 (±8.89) years and mean years of teaching of 10.75 (±8.52) years. Regarding specialties, 24 (46.15%) were professors of D, 23 (44.23%) were professors of PD, and 5 (9.62%) were professors of D and PD. Thirteen (25%) had a master’s degree in clinical dentistry (CD), 12 (23.08%) had a master’s degree in D, 8 (15.39%) had a master’s degree in PD, 7 (13.45%) had a master’s degree in dental materials (DM) and 12 (23.08%) had master’s degrees in other areas. Eight professors had doctoral degrees in each CD (15.38%) and D (15.38), followed by 6 (11.54%) professors with doctoral degrees in DM, 2 (3.85%) with doctoral degrees in PD, and 28 (53.85%) with doctoral degrees in other areas. Most professors [29 (55.77%)] taught in private institutions, 18 (34.62%) taught in public institutions, and 5 (9.62%) taught in both. In addition to teaching, 35 (67.31%) worked in private practice, 16 (30.77%) worked exclusively as teachers, and 1 (1.92%) did not respond to the question. Regarding teaching, 38 (73.08%) professors taught theoretical, laboratory and clinical classes, 7 (13.46%) taught theoretical and clinical classes, 2 (3.85%) taught theoretical and practical classes in the laboratory, 2 (3.85%) taught only clinical practices, 1 (1.92%) taught only laboratory practices, 1 (1.92%) taught laboratory and clinical practices, and 1 (1.92%) taught only theoretical classes. Regarding the syllabus for D and PD, the CAD-CAM system was addressed by 29 (55.77%) professors. Of these, 26 (50%) taught only in theoretical classes, and 3 (5.77%) taught in theoretical and practical classes. CAD-CAM content was not taught by 23 (44.23%) respondents. In clinical activities, only 8 (15.38%) professors performed procedures using CAD-CAM with their students, and 44 (84.62%) did not perform any procedures using CAD-CAM. The conclusion is that CAD-CAM content is little explored in the undergraduate teaching of these courses, being restricted to theoretical classes and not being a reality in clinical practice; a worrying lack of content in the profile of graduates.